Continuous, crystalline Sb2S3 ultrathin light absorber coatings in solar cells based on photonic concentric p-i-n heterojunctions. (1st December 2022) - Büttner, Pascal; Scheler, Florian; Döhler, Dirk; Barr, Maïssa K.S.; Bosch, Michael; Rey, Marcel; Yokosawa, Tadahiro; Hinz, Sandra; Maultzsch, Janina; Spiecker, Erdmann; Vogel, Nicolas; Mínguez-Bacho, Ignacio; et al.
Abstract: Many modern types of solar cells that rely exclusively on earth-abundant non-toxic materials include interfaces between a heavier metal chalcogenide and another type of semiconductor. Often, the chemical (adhesion) and physical (charge transfer) characteristics of those interfaces are the defining factors for the final device performance. Here, we describe that a ZnS adhesion layer is not sufficient to prevent the dewetting of Sb2 S3 upon annealing a thin layer of it on an oxidic surface if the substrate is not planar and features highly curved surfaces. An ALD-coated sacrificial capping layer of ZnO prevents the morphological rearrangements of Sb2 S3 during thermal crystallization and can be removed subsequently. When implemented towards a photovoltaic p-i-n heterojunction, this strategy furnishes perfect conformality of the layer stack but unsatisfactory performance. The correlation of interface chemistry with the electrical properties and the device performance identifies a reducing effect of ZnO atomic layer deposition chemistry on the Sb2 S3 surface as the cause of Zn diffusion into the light absorbing semiconductor. This deleterious doping can be prevented by a preliminary oxidative treatment of the Sb2 S3 surface with ozone. When applied to a structured substrate consisting of ordered arrays of nanospheres, this approach yields the first ever concentric p-i-n heterojunction solar cells with photonic light trapping effect—a geometry which in comparison with standard scattering layers'on top' inherently generates a very large refractive index contrast. In the red part of the visible spectrum, light absorption amounts to the value expected with four passes through a planar layer of the thickness used here (35 nm Sb2 S3 ). This effect allows us to demonstrate > 5% overall solar energy conversion efficiency with only 35 nm of a simple light absorber phase that uses no toxic, rare materials. Graphical abstract: Highlights: A confined crystallization method yields conformal stibnite Sb2 S3 coatings. Fine tuning of the interface chemistry can either resolve or promote interface reactions and gradient doping. Efficient ultrathin solar cells on nanosphere concentric p-i-n heterojunctions. Light trapping by photonic nanostructure increases photocurrent with 35 nm absorber.